1997
DOI: 10.1063/1.119247
|View full text |Cite
|
Sign up to set email alerts
|

Domain-orientation dependence of levitation force in seeded melt grown single-domain YBa2Cu3Ox

Abstract: Domain-orientation dependence of levitation force has been determined for single-domain YBa2Cu3Ox. The single-domain material is obtained from a seeded melt growth process. The levitation force has been found to reach a maximum as the c axis of the domain is parallel to the direction of the force. The levitation force decreases in a cosine law fashion as the angle θ (the angle between the direction of the force and the c axis) increases from 0° to 60°. A maximum anisotropy of levitation force of 2.29 has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…HTSs are highly anisotropic, with superconducting currents capable of flowing at higher density in the ab plane of the crystal. With the ability to grow large singledomain HTSs, the angle dependence of crystal orientation on levitation force has recently been explored [47][48][49][50]. For melt-textured YBCO, this anisotropy results in a levitation force that is ≈3 times greater if the c axis is parallel to a uniform applied field, than if the c axis is perpendicular to the applied field.…”
Section: Effects Of Geometrymentioning
confidence: 99%
“…HTSs are highly anisotropic, with superconducting currents capable of flowing at higher density in the ab plane of the crystal. With the ability to grow large singledomain HTSs, the angle dependence of crystal orientation on levitation force has recently been explored [47][48][49][50]. For melt-textured YBCO, this anisotropy results in a levitation force that is ≈3 times greater if the c axis is parallel to a uniform applied field, than if the c axis is perpendicular to the applied field.…”
Section: Effects Of Geometrymentioning
confidence: 99%
“…Detailed experiments have been performed on melt-textured-grown ͑MTG͒ YBCO and RBCO (R denotes a rare earth element such as Nd, Sm, Gd, Eu, Dy, Ho, Er, Tm, Yb, Lu, and La͒, thin films, as well as granular samples. 4,[12][13][14][15][16] For MTG YBCO and RBCO samples, the force curve is usually asymmetrical, i.e., the absolute value of the attractive force is smaller than the maximum repulsive force ͉F a,max ͉ϽF r,max . 16 For thin films, the force curve is almost symmetrical ͉F a,max ͉ϷF r,max , 17 while for granular samples, the attractive force is hardly present.…”
Section: Introductionmentioning
confidence: 99%
“…25 Other characteristics of the HTS, such as the anisotropy and the grain orientation inside the MTG samples have been studied and shown to affect the levitation force. 14,26 The stiffness of the PM-HTS system, which represents the spring constant associated with vibrational motion of the levitation system has been intensively studied. Experimental results for vertical stiffness, lateral stiffness and cross stiffness have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…But up to now, there are only a few reports available on the crossing phenomenon in the force-distance hysteretic curve. Moreover, it is well known that the levitation force between a superconductor and a magnet is not only related to the electromagnetic properties of the superconductor, but also to the thickness and shape of the samples [14], initial cooling process [15,16], operating temperature [17], grain-orientation [18] etc. Postrekhin et al [19] reported the dependence of the levitation force on the average speed of moving the magnet (up to 12 mm/s) towards the superconductor and found that the maximum levitation force increased with increase in the moving speed of the magnet.…”
Section: Introductionmentioning
confidence: 99%